Evolutionary Macroeconomics (Routledge Revivals). - Foster, John (Routledge revivals., 2013)
First published in 1987, Evolutionary Macroeconomics offers an evolutionary approach to macroeconomics as an alternative to contemporary new classical and Keynesian macroeconomics.